Geotechnical engineering handbook - Smoltczyk, Ulrich (Ernst & Sohn, 2002)
The second volume of the Geotechnical Engineering Handbook deals with the goetechnical methods for the installation of anchors, piles, micro-tunnels and earthworks, and for ground improvement, underpinning of existing structures, dewatering and excavation of rock material. Special chapters describe the applicaiton of geosynthetics and biological measure in ground engineering. The first English edition is based on earlier German editions but with several new authors and with due adaption in favour of the English speaking profession.